2020
DOI: 10.4317/medoral.23498
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of PTEN promoter methylation in ameloblastoma

Abstract: Background: Phosphatase and tensin homolog (PTEN) acts as a tumor suppressor gene. Inactivation of PTEN has been reported in various types of cancers. PTEN promoter methylation possibly underlies PTEN inactivation, which results in tumorigenesis. The aim of this study was to investigate whether PTEN promoter methylation contributes to PTEN inactivation in ameloblastoma and its associated protein expression. Material and Methods: In total, 20 fresh-frozen ameloblastoma samples were evaluated for PTEN promoter m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
1
16
0
1
Order By: Relevance
“…MSH2 and MSH6 showed a negative correlation between the methylation status and their respective immunohistochemistry expression, similar to that observed in sporadic colorectal cancer (Malhotra et al., 2014). However, the same correlation was not observed with the MSH3 analysis, suggesting that other mechanisms might be involved in this gene regulation as were reported with the PTEN gene in ameloblastoma (Lapthanasupkul et al., 2020). The current sample size could be a limitation in our study what could explain the lack of the statistical significance detected for MSH3.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…MSH2 and MSH6 showed a negative correlation between the methylation status and their respective immunohistochemistry expression, similar to that observed in sporadic colorectal cancer (Malhotra et al., 2014). However, the same correlation was not observed with the MSH3 analysis, suggesting that other mechanisms might be involved in this gene regulation as were reported with the PTEN gene in ameloblastoma (Lapthanasupkul et al., 2020). The current sample size could be a limitation in our study what could explain the lack of the statistical significance detected for MSH3.…”
Section: Discussionsupporting
confidence: 67%
“…analysis, suggesting that other mechanisms might be involved in this gene regulation as were reported with the PTEN gene in ameloblastoma (Lapthanasupkul et al, 2020). The current sample size could be a limitation in our study what could explain the lack of the statistical significance detected for MSH3.…”
Section: Muts Genes Methylation Status and Muts Immunohistochemistry ...mentioning
confidence: 67%
“…Finally, we identified some regulatory pairs with prognostic significance in several cancers. Moreover, studies have reported that differential expression or methylation is highly related with tumorigenesis through regulating gene expression (69)(70)(71)(72). Our study identified miRNAs/probes that were differentially expressed/methylated between tumor and normal samples, indicating their potential association with tumorigenesis.…”
Section: Discussionmentioning
confidence: 63%
“… 27 PTEN acts as a tumor suppressor gene and inactivation of PTEN has been reported in various types of cancers. 28 In order to verify the effect of PTEN, the shRNA-PTEN was transfected into the cells with low expression of miR-130a, and the proliferation and migration of SCC-4 cells were significantly increased after downregulating PTEN at the same time, indicating that downregulating PTEN could reverse the inhibition of miR-130a on the proliferation and migration of SCC-4 cells. PTEN expression was seen to be downregulated in OSCC cells.…”
Section: Discussionmentioning
confidence: 99%